Association between dietary fiber intake and all-cause and CVD-caused mortality among heart failure survivors: a cohort study from the NHANES database - Shulin Wang; Yun Ruan; Yuliang Zhang (Frontiers in Cardiovascular Medicine)
AimHeart failure (HF) is a severe manifestation or late stage of various heart diseases. As an anti-inflammatory nutrient, dietary fiber has been shown to be associated with the progression and prognosis of cardiovascular diseases (CVDs). However, little is known about the relationship between dietary fiber intake and mortality in HF survivors. This study evaluated the association between dietary fiber intake and all-cause and CVD-caused mortality among HF survivors.MethodsData for the study were extracted from the National Health and Nutrition Examination Survey 1999–2018. Dietary fiber intake information was obtained by a 24-h dietary recall interview. Death outcomes were ascertained by linkage to National Death Index records through 31 December 2019. Covariates, including sociodemographic, lifestyle, disease history, and laboratory data, were extracted from the database. The weighted univariate and multivariate Cox proportional hazard models were utilized to explore the association between dietary fiber intake and mortality among HF survivors, with hazard ratios and 95% confidence intervals. Further stratified analyses were performed to explore this association based on age, gender, a history of diabetes and dyslipidemia, and duration of HF.ResultsA total of 1,510 patients were included. Up to 31 December 2019, 859 deaths had occurred over a mean follow-up of 70.00 months. After multivariable adjustment, a higher dietary fiber intake was associated with a lower risk of all-cause and CVD-caused mortality in HF survivors, especially in male patients, those aged <60 years old, and those with a history of diabetes and dyslipidemia.ConclusionAmong HF survivors, higher dietary fiber intake levels may be associated with a good health outcome. More large-scale prospective cohort studies are needed to further explore this benefit relationship.